Relationship Between Conditional Volatility of Domestic Macroeconomic Factors and Conditional Stock Market Volatility: Some Further Evidence from India - Kumari, Jyoti; Mahakud, Jitendra (Asia-Pacific financial markets, 2015)
The present paper empirically examines the theoretical linkage between stock market volatility and macroeconomic volatility in emerging Indian stock market covering the data period from July 1996 to March 2013. Unlike the previous studies, the present study investigates the issue with two stage estimation techniques. Conditional volatility is extracted by employing univariate autoregressive conditional heteroskedasticity models. Further, multivariate VAR model along with impulse response function, block exogeneity and variance decomposition are carried out to analyze the relationship between stock market volatility and macroeconomic volatility. Data on macroeconomic variables namely output, foreign institutional investments, exchange rate, short term and long-term interest rates, broad money supply, inflation and stock market indices BSE Sensex and NSE Nifty are used for analysis. The findings suggest a linkage between macroeconomic volatility and equity market volatility.